THU0590 The Patient-Therapist Relationship as An Indicator for Treatment Success in E-Health Treatments for Patients with Rheumatoid Arthritis and Psorias. (23rd January 2014) - Ferwerda, M.; Spillekom, S.; van Middendorp, H.; van Beugen, S.; Kievit, W.; Fransen, J.; Visser, H.; van Oijen, P.; Taal, E.; van Riel, P.; de Jong, E.; van de Kerkhof, P.; et al.
Abstract : Background: The popularity of E-health is rising and research has shown that E-health interventions can be effective [1 ]. However, they also offer new challenges and questions in clinical practice and research, for example about the role of the patient-therapist relationship [2, 3 ]. In face-to-face treatments, a better patient-therapist relationship has often been reported as a predictor for improved treatment outcome. Objectives: In an E-health cognitive-behavioral treatment for patients with rheumatoid arthritis and psoriasis, the patient-therapist relationship was assessed and related to patient-reported outcomes. Methods: After a face-to-face intake, all patient-therapist contact was through e-mail. Patients rated the patient-therapist relationship pre and post treatment using the Working Alliance Inventory and internet-specific relationship questions. After treatment, patients were asked to rate improvement in symptoms and coping with these symptoms. Paired samples t-tests (patient-therapist relationship change during treatment) and regression analyses (association patient-therapist relationship and patient-reported outcome) were performed in a subsample of patients who had finished treatment. Results: The patient-therapist relationship was rated positively and increased during treatment (p <.05) as generally found in face to face treatments. Both a better patient-therapist relationship and the specific internet related aspects (e.g., having time to think about the reply to the therapist) predicted patient-reported improvement in coping with disease problems, such as pain and fatigue (p-values <.05). At the end of treatment both relationship aspects are related to improvements in symptoms and coping with these symptoms (all p-values <.05). Conclusions: These preliminary results indicate that the patient-therapist relationship is a possible predictor for self-reported improvements in E-health treatments, similar to the role of this patient-therapist relationship in face-to-face treatments. Future results need to demonstrate whether the patient-therapist relationship also contributes to the cost-effectiveness of this E-health treatment in the randomized controlled trial. References: Cuijpers, P., Straten, A., & Andersson, G. Internet-administered cognitive behavior therapy for health problems: A systematic review. Journal of Behavioral Medicine 2008;31:169-77. Martin, D.J., Garske, J.P., & Davis, M.K. Relation of the therapeutic alliance with outcome and other variables: A meta-analytic review. Journal of Counseling and Clinical Psychology 2000;68:438-50. Preschl, B., Maercker, A., & Wagner, B. The working alliance in a randomized control trial comparing online with face-to-face cognitive behavioral therapy for depression. BMC Psychiatry 2011;11:189. Acknowledgements: We would like to thank the patient representatives Henk van Duijn, Mariëtte Tomas, and Hen Ros for their contributions to the study, and ZonMw (The Netherlands Organisation for Health Research and Development) and Pfizer Inc. for their financial contribution to this research project. Disclosure of Interest: M. Ferwerda Grant/research support from: Pfizer Inc., S. Spillekom: None Declared, H. van Middendorp: None Declared, S. van Beugen Grant/research support from: Pfizer Inc., W. Kievit: None Declared, J. Fransen: None Declared, H. Visser: None Declared, P. van Oijen: None Declared, E. Taal: None Declared, P. van Riel Consultant for: Roche, Abbott, Pfizer, E. de Jong: None Declared, P. van de Kerkhof: None Declared, M. van der Laar: None Declared, A. Evers Grant/research support from: Pfizer Inc., Consultant for: Roche